Kappa opioid agonists reduce oxycodone self-administration in male rhesus monkeys - Zamarripa, C. Austin; Naylor, Jennifer E.; Huskinson, Sally L.; Townsend, E. Andrew; Prisinzano, Thomas E.; Freeman, Kevin B. (Psychopharmacology, 2020)
Rationale Combinations of mu and kappa opioid receptor (KOR) agonists have been proposed as potential analgesic formulations with reduced abuse liability. The current studies extend previous work by investigating the typical KOR agonist, salvinorin A, and the atypical KOR agonist, nalfurafine, as deterrents of oxycodone self-administration using a progressive ratio (PR) schedule of reinforcement. Methods In separate experiments, adult male rhesus monkeys ( N = 4/experiment) were trained under a PR schedule of reinforcement to self-administer cocaine (0.1 mg/kg/injection) and saline on alternating days. Oxycodone (0.01–0.1 mg/kg/injection) alone and combined with salvinorin A (experiment 1; 0.006, 0.012 mg/kg/injection) or nalfurafine (experiment 2; 0.0001–0.00032 mg/kg/injection) were tested within the alternating cocaine and saline baseline. The mechanism of nalfurafine’s effects on oxycodone self-administration was investigated via pretreatment with the KOR antagonist, nor-binaltorphimine (nor-BNI; 10 mg/kg; i.m.). Results All subjects self-administered oxycodone alone above saline levels at sufficiently large doses, and combining salvinorin A or nalfurafine with oxycodone reduced the mean number of injections per session to saline levels (experiment 1) or to levels that were significantly lower than oxycodone alone (experiment 2). The ability of nalfurafine to reduce oxycodone self-administration was reversed by pretreatment with nor-BNI. Conclusions These results demonstrate that KOR agonists, including the clinically used KOR agonist, nalfurafine, can punish self-administration of a prescription opioid analgesic, oxycodone, in rhesus monkeys and that nalfurafine’s punishing effect is KOR-dependent. Combinations of KOR agonists with prescription opioids may have reduced abuse liability.